PENGARUH DANA ALOKASI UMUM (DAU) TERHADAP PERTUMBUHAN EKONOMI - Ari Ginting (Pusat Kajian Anggaran, 2016)
General Allocation Fund (DAU) is part of the fiscal decentralization by Central Government to local government. Based on data from Central Bank, nearly 81% of local government financial in North Sumatera are supported by the DAU provided from Central Governmnet. This study had 2 goals, the first goal is to determine the development of local revenue and expenditure and the second goal is to analyze the influence of DAU to local government in Nort Sumatera. This reseach used 33 data from local government in North Sumatera from 2006 to 2015 and using panel regression. This reseach found that from APBD in local government in North Sumatra are rely mostly on DAU rather then PAD. And the local government expenditure are alocated for operasional expenditure rahter than capital expenditure. Based on panel regression found that the growth of DAU and BM has positive and significant impact on local economic growth. The local government have to shift the political will from operasional expenditure into capital expenditure, so it will effect on economic growth and public welfare.